Analisis Pengaruh Dana Pihak Ketiga (DPK) dan Non Performance Financing (NPF) Terhadap Profitabilitas dengan Tingkat Inflasi sebagai Variabel Moderating pada PT. BANK SUMUT Unit Usaha Syariah di Sumatera Utara - Wilkin Dody Ginting; Irfan; Dahrani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted with the aim of testing and analyzing the effect of third party funds and Non Performance Financing on profitability moderated by the inflation rate directly and moderately. The population in this study were all branches of PT. Bank Sumut Sharia Business Unit in North Sumatra as many as 6 branch offices and samples using 6 branch offices for five years so that 30 data were obtained. This research approach uses associative research. Data collection techniques in this study use documentation techniques. and the analysis techniques used are multiple linear regression analysis, hypothesis testing, coefficient of determination and Moderated Regression Analysis using the Eviews 13 program. The results of the study indicate that third party funds partially affect profitability, Non Performance Financing does not affect profitability, Furthermore, the inflation rate does not moderate third party funds and Non Performance Financing on profitability at PT. Bank Sumut Sharia Business Unit in North Sumatra.